Referendum models and economic values: theoretical, intuitive, and practical bounds on willingness to pay. - Haab, Timothy C.; McConnell, Kenneth E. (Land Economics, 1998)
A set of criteria is proposed that guarantees a bounded measure of willingness-to-pay (WTP) in contingent valuation models and rejects the traditional random utility model with unrestricted error terms in favor of the random WTP model with bounds on WTP. Analysis indicates that when WTP is bounded by zero and income, the form of the distribution is less consequential. A new model for WTP is developed based on the beta distribution, and a comparison between it and previously estimated models is presented.